Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Assessments of Tensile Characteristics and Degradation Mechanism of Sandstone Subjected to Wetting–Drying Cyclic Treatment - Rui Li; Changtai Zhou; Yizi Fu; Jianbo Zhu (Rock Mechanics and Rock Engineering, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

4-Phenylbutyric acid may prevent mouse ovarian and uterine damage due to procymidone-induced alteration of circRNA Scar and circZc3h4 levels by controlling excessive unfolded protein response - Rui Li; Fan Li; Xuning Wang; Mingxin Bai; Hu Fu; Zhengli Yan; Xiaoping Yang; Yongfei Zhu (Pesticide Biochemistry and Physiology, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Modulation of soy protein immunoreactivity by different matrix structures of lactic acid bacterium-induced soy protein gels: Epitope destruction during in vitro gastroduodenal digestion and absorption - Yaqiong Wang; Yumeng Fu; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Fruit detachment force of multiple varieties kiwifruit with different fruit-stem angles for designing universal robotic picking end-effector - Wentai Fang; Zhenchao Wu; Weiwu Li; Xiaoming Sun; Wulan Mao; Rui Li; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Twice matched fruit counting system: An automatic fruit counting pipeline in modern apple orchard using mutual and secondary matches - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Fangfang Gao; Rui Li; Longsheng Fu; Dong Zhang; Spyros Fountas (Biosystems Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Mechanism analysis and improved molecular modification: Design of high efficiency and environmentally friendly triazole fungicide substitutes - Jiaxuan Gao; Xinao Li; Rui Fu; Yu Li (Chemosphere, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Energy-oriented control retrofit for existing HVAC system adopting data-driven MPC – Methodology, implementation and field test - Bao Yue; Bing Su; Fu Xiao; Anbang Li; Kehua Li; Shen Li; Rui Yan; Qiuzhuang Lian; Ao Li; Yuanyang Li; Xing Fang; Xingang Liang (Energy and Buildings, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

A new oleanane-type triterpene from Ardisia lindleyana D.Dietr and its cytotoxic activity - Zhou Tiqiang; Wei Zhenzhen; Fu Qianyu; Qiu Rui; Zhang Guangjie; Li Bin; Dong Junxing; Zeng Chengchu (Natural Product Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

NDMFCS: An automatic fruit counting system in modern apple orchard using abatement of abnormal fruit detection - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Wulan Mao; Rui Li; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Satellite observed response of fire dynamics to vegetation water content and weather conditions in Southeast Asia - Yuyun Fu; Jiheng Hu; Weiguo Song; Yuanxi Cheng; Rui Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Screening eco-friendliness tire antioxidants alternatives: functional 2,2,4-trimethyl-1,2-dihydroquinoline derivatives design and toxicity evaluation - Yu Wang; Rui Fu; Peixuan Sun; Xinao Li; Wenjin Zhao (Environmental Science and Pollution Research, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Innovative screening for functional improved aromatic amine derivatives: Toxicokinetics, free radical oxidation pathway and carcinogenic adverse outcome pathway - Yajing Liu; Xinao Li; Qikun Pu; Rui Fu; Zhonghe Wang; Yu Li; Xixi Li (Journal of Hazardous Materials, 2023)

Potential thyroid hormone disorder risks of tire antioxidants to aquatic food chain organisms after absorbing free radicals in marine and freshwater environments - Yu Wang; Rui Fu; Xinao Li; Wenjin Zhao; Miao Liu; Yu Li (Aquatic Toxicology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Thin wire segmentation and reconstruction based on a novel image overlap-partitioning and stitching algorithm in apple fruiting wall architecture for robotic picking - Hanhui Jiang; Xiaoming Sun; Wentai Fang; Longsheng Fu; Rui Li; Fernando Auat Cheein; Yaqoob Majeed (Computers and Electronics in Agriculture, 2023)

Phenotyping of individual apple tree in modern orchard with novel smartphone-based heterogeneous binocular vision and YOLOv5s - Guanao Zhao; Ruizhe Yang; Xudong Jing; Haosen Zhang; Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Rui Li; Xiaofeng Wei; Spyros Fountas; Huijun Zhang; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Genome-Wide Identification and Expression Analysis of the CAD Gene Family in Walnut (Juglans regia L.) - Pengyu Wu; Rui Zhang; Shangqi Yu; Jiazhi Fu; Zhongzhong Guo; Dong Li; Zhiyong Pan; Haifang Hu (Biochemical Genetics, 2023)

Growth, nutrient uptake and transcriptome profiling of rice seedlings in response to mixed provision of ammonium- and nitrate-nitrogen - Youqiang Fu; Xuhua Zhong; Chusheng Lu; Kaiming Liang; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Qunhuan Ye; Yanzhuo Liu (Journal of Plant Physiology, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A novel pollination robot for kiwifruit flower based on preferential flowers selection and precisely target - Changqing Gao; Leilei He; Wentai Fang; Zhenchao Wu; Hanhui Jiang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to “Limited hydrolysis of glycosylated whey protein isolate ameliorates the oxidative and physical stabilities of conjugated linoleic acid oil-in-water emulsions” [Food Chem. 362 (2021)130212] - Meng Li; Rui Yu; Runxiao Fu; Yanting He; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)